Three-Dimensional Discontinuum Analysis of Structurally Controlled Failure Mechanisms at the Cadia Hill Open Pit - Sainsbury, D; Pothitos, F; Finn, D; Silva, R (Slope Stability 2007: Proceedings of the 2007 International Symposium on Rock Slope Stability in Open Pit Mining and Civil Engineering, 2007)
The south wall of Newcrest Mining Ltd’s Cadia Hill Open Pit experienced a multi-bench (60,000 t) failure during 2006. The observed failure mechanism is a combination of structurally controlled and rock mass failure. The 3DEC code has been developed by Itasca specifically to study complex failure mechanisms involving large numbers of explicit structures (joints, faults) that divide a rock mass into blocks. Slip, separation and rotation along explicit structures can occur, while the individual blocks can also deform and yield. The following paper details a series of analyses that have been conducted with 3DEC to back-analyse the observed behaviour of the south wall, which happened when mining was at the 505 RL level. The calibrated model has subsequently been used to investigate the behaviour of the south wall after mining has progressed down to the 445 RL level.